16.8k views
3 votes
6y – 5 = –3(2y + 1) please solve

2 Answers

3 votes

Steps to solve:

6y – 5 = –3(2y + 1)

~Distribute left side

6y - 5 = -6y - 3

~Add 5 to both sides

6y = -6y + 2

~Add 6y to both sides

12y = 2

~Divide 12 to both sides

y = 1/6

Best of Luck!

User Granny Aching
by
4.2k points
1 vote

Answer:


y=1/6

Explanation:

So we have the equation:


6y-5=-3(2y+1)

First, distribute the right side:


6y-5=-6y-3

Add 6y to both sides. The right cancels:


12y-5=-3

Add 5 to both sides. The left cancels:


12y=2

Divide both sides by 12:


y=2/12

Reduce:


y=1/6

And we're done!

User Nichola
by
5.1k points